Determination of peaking factors for sewerage system in Antalya, tourism capital of Turkey - Tan, Remziye Ilayda; Arslankaya, Ertan; Kesgin, Erdal; Agaccioglu, Hayrullah (WILEY, 2021)
The design of wastewater system pipe size is traditionally based on the maximum wastewater flow that is a function of multiple factors. Understanding the appropriate peaking factors (PF) by using daily flow variations through wastewater collection systems (WWCS) is essential for cost-effective design. This paper describes the maximum and minimum PFs by using wastewater flow data of four separate residential areas such as Lara, Belek-1, Kemer, and Hurma in Antalya, which is the tourism capital of Turkey. The study involves the analysis of wastewater data recorded at daily interval for two different time periods (2006-2009 and 2016-2019) in Antalya. There is a comprehensive investigation regarding PFs that involves sustained peaking flow and percentiles. Therefore, a new empirical equation was proposed by using wastewater flowrate for the estimation of the maximum daily peaking factor. When the daily PFs are determined in the range of 1.31-1.52, 1.60-2.58, 2.26-3.29, and 1.93-2.29 for Lara, Belek-1, Kemer, and Hurma wastewater treatment plants (WWTPs) for 2016-2019 time period, they are in the range of 2.19-2.93 and 1.95-3.31 for Lara and Hurma WWTPs for the time period of 2006-2009, respectively. In brief, this study presents a comprehensive calculation of PFs with a determination of their sustained flow analysis with different durations and percentiles. Practitioner Points This study presents the findings regarding peaking factors and its statistical analysis for different time periods. Statistical analysis included sustained flow, and the percentile of peaking factors was applied to waste water flow data for touristic city of Antalya. The new formula of PFmax,dry=39.18.(Qav,d)-0.32 was determined by using more touristic areas of Antalya within the scope of estimation of the daily peaking factor for dry weather flow by using average daily wastewater flowrate data with the determination coefficient of 0.95.
Keywords: flow; peaking factor; percentile; sustained flow; wastewater; WWTP; Engineering; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources